Microsoft Visual Basic 2005 : for Windows, mobile, web, office, and database applications - Shelly, Gary B.
Microsoft Visual Basic 2005 for Windows, Mobile, Web, Office, and Database Applications: Comprehensive is the first text of its kind to teach students the essentials of computer programming using the latest Visual Basic programming language, Visual Basic 2005. Thirteen chapters cover topics such as designing a Visual Basic user interface, creating a windows application, variables and arithmetic operations, mobile applications using decision structures, loop structures, Web applications with ASP 2.0 and string manipulation, Visual Studio tools for Office applications, arrays, function procedures and exception handling, incorporating databases with ADO.NET, creating classes, and cell phone applications and Web services. Written in a straight-forward style, this text makes it easy for any novice programmer to understand the core capabilities and fundamental techniques for Visual Basic 2005